The psychometric properties of students’ attitudes, coping strategies, and psychological symptoms - Roslee Ahmad; Dede Rahmat Hidayat; Susi Fitri; Lokman Mohd Tahir; Mohd Faizal Kasmani; Rezki Perdani Sawai; Hizral Tazzif Hisham; Mohd Izwan Mahmud (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study examined the psychometric elements of psychological symptoms, attitudes and coping strategies and the impact of COVID-19 on learning among the university students in Malaysia. The design employed in this study was survey method, that centered on convenience sampling method. A total of 489 students from eight undergraduate program of year 1 to year 4 participated in the study. They enrolled in various disciplines ranging from chemical and food science, medicine, engineering, psychology, communication to religious studies program. Data was analyzed using exploratory factor analysis (EFA) with all items being grouped within the study’s constructs, which subsequently, were tested using the establishment of measurement model of confirmatory factor analysis. The instrumentation for this study was adapted from Weiner’s Attribution Theory, Expectations and Values Theory. Comparatively, in measuring the students’ coping strategic approach, items were adopted from Greenaway. Additionally, the Counseling Center Assessment of Psychological Symptoms (CCAPS-62) scale was adapted to measure the eight constructs namely anxiety, social anxiety, academic distress, eating anxiety distress, family distress, hostility, and smoking abuse. The Cronbach’s alpha values for all three constructs have indicated the accepted values. Findings revealed that the loading factors for the attitude, coping strategies and psychological constructs are at the accepted values and acceptable composite reliability values. Findings also indicate that the measurement model for the construct attitude, coping strategies and psychological have loading estimates that are statistically significant.